Femtosecond Time-Resolved Stimulated Raman Spectroscopy of the S(2) (1B(u)) Excited State of beta-Carotene. - Kukura, P; McCamant, D; Mathies, R (2004)
The electronic and vibrational structure of beta-carotene's early excited states are examined using femtosecond time-resolved stimulated Raman spectroscopy. The vibrational spectrum of the short-lived ( approximately 160 fs) second excited singlet state (S(2),1B(u) (+))of beta-carotene is obtained. Broad, resonantly enhanced vibrational features are observed at approximately 1100, 1300, and 1650 cm(-1) that decay with a time constant corresponding to the electronic lifetime of S(2). The temporal evolution of the vibrational spectra are consistent with significant population of only two low-lying excited electronic states (1B(u) (+) and 2A(g) (-)) in the ultrafast relaxation pathway of beta-carotene.